Dataset associated with "Enhancements in ammonia and methane from agricultural sources in the northeastern Colorado Front Range using observations from a small research aircraft" - Pollack, Ilana; McCabe, Megan; Caulton, Dana; Fischer, Emily V. (Colorado State University. Libraries, 2021)
Quantifying ammonia (NH3) to methane (CH4) enhancement ratios from agricultural sources is important for understanding air pollution and nitrogen deposition. The northeastern Colorado Front Range is home to concentrated animal feeding operations (CAFOs) that produce large emissions of NH3 and CH4. Isolating enhancements of NH3 and CH4 in this region due to agriculture is complicated because CAFOs are often located within regions of oil and natural gas (O&NG) extraction that are a major source of CH4 and other alkanes. Here, we utilize a small research aircraft to collect in-situ 1-Hz measurements of gas-phase NH3, CH4, and ethane (C2H6) downwind of feedlots during three flights conducted in November 2019. Enhancements in NH3 and CH4 are distinguishable up to 10 km downwind of CAFOs with the most concentrated portions of the plumes typically below 0.25 km AGL. We demonstrate that NH3 and C2H6 can be jointly used to separate near-source enhancements in CH4 from agriculture and O&NG. Molar enhancement ratios of NH3 to CH4 are quantified for individual CAFOs in this region, and they range from 0.8 - 2.7 ppbv ppbv-1. A multivariate regression model can be used to attribute the relative contribution of O&NG versus agriculture during the brief study period.
Data collected in flight aboard the University of Wyoming King Air research aircraft. The data are from three 2-4 hour flights that occurred on November 9, November 13, and November 15 in 2019. The dataset includes timeseries of trace gases (specifically ammonia, methane, ethane, carbon monoxide, and carbon dioxide) and meteorological and position variables routinely recorded by the aircraft. The flights were conducted in the northeastern Colorado Front Range. A goal of the flights was to sample emissions from agricultural facilities in the area and separate them from other sources in the region, such oil and natural gas production.
Department of Atmospheric Science
Keywords: ammonia; methane; enhancement ratios; agricultural emissions; concentrated animal feeding operations; oil and natural gas; northeastern Colorado Front Range; multivariate regression